The activities of the soviet special commission on refugees in Semirechye in the 20s of the XX century (Journal of history, 2024)
The fate of the refugees of the first quarter of the 20th century, who participated in the uprisings in Zhetysu and were forced to flee their homeland, is a little-studied topic in the history of political cataclysms in Kazakhstan. The purpose of the proposed article is to reconstruct the activities of the special commission of the Central executive Committee of the Turkestan Republic, whose purpose was the return and accommodation of refugees from the Zhetysui region who left the cordon after the uprising of 1916 and the first years of the establishment of Soviet power in Russia, primarily to Western China. The evolution of the Soviet position in connection with the return of refugees from the policy of retaliation by the authorities of Tsarist Russia for the national liberation uprising in the region and the continued persecution of the indigenous population in the early years of the establishment of Soviet power depended entirely on the internal socio-political and geopolitical situation. In the course of the study, a descriptive method was used that contributes to the formation of a real-life image. The descriptive method allows us to delve into the historical reasons for the formation and periodization of refugee as a phenomenon. As a result of the scientific research, the conditions for the creation, aspects and structure of the activities of the Soviet special commission for the return of refugees were systematized for the first time. The situation of refugees in the host country was examined on the basis of evidence. The socio-economic and political reasons for the measures for the return and placement of refugees, its progress and results are analyzed using important sources from the funds of foreign and domestic republican archives, as well as special funds of regional archives directly related to the object of research. For the first time in Russian historical science, the scientific study analyzes the degree of interaction, the reasons for the contradiction of the position of Soviet civil, military and diplomatic structures on solving the refugee problem in the 20s of the XX century. The results of the research can be used in special courses, textbooks, educational publications on the humanitarian field of higher educational institutions on the problems of social history and migration of the first quarter of the 20th century.Key words: Kazakh-Kyrgyz refugees, Xinjiang Province, special commission, Ili Protocol, sub-commissions, border counties, refugees sold into slavery.